Rapid Effect of Gamma Knife Radiosurgery on Clivus Metastasis: A Case Report - (:unkn) unknown (GEORG THIEME VERLAG KG, 2016)
Breast cancer may cause distant metastasis even though there is no local recurrence. Disease can spread to any part of body via lymphoid and hematogenous way, and clivus is one of the most common locations. Total excision of clival lesions carries a significant risk of neurologic damage due to proximity to cranial nerves. We present 62-year-old woman who has a previously known breast cancer history. She admitted to our clinic with unilateral sixth nerve palsy and diplopia. Imaging studies revealed clivus metastasis. Patient was treated with gamma knife radiosurgery. In the next 2 months, sixth nerve palsy recovered along with diplopia. In this case report we would like to emphasize the importance of gamma knife radiosurgery at the deeply located breast cancer metastasis.
Keywords: clivus; radiosurgery; metastasis; PATTERNS